Case Report: Use of Obinutuzumab as an Alternative Monoclonal Anti-CD20 Antibody in a Patient With Refractory Immune Thrombocytopenia Complicated by Rituximab-Induced Serum Sickness and Anti-Rituximab Antibodies - Blase, Jennifer R.; Frame, David; Michniacki, Thomas F.; Walkovich, Kelly (Frontiers in Immunology, 2022)
Management of refractory immune thrombocytopenia frequently involves rituximab, a chimeric anti-CD20 monoclonal antibody, to target B cells and induce remission in most patients. However, neutralizing antibodies to rituximab that nullify therapeutic response and may lead to serum sickness have been rarely reported. Here, we present a case of a young adult female with Evans syndrome treated with rituximab, complicated by the development of serum sickness, acute respiratory distress syndrome and platelet refractoriness presumed secondary to neutralizing antibodies to rituximab. She was successfully treated with the humanized anti-CD20 monoclonal antibody, obinutuzumab, with subsequent symptom resolution. Additionally, a review of 10 previously published cases of serum-sickness associated with the use of rituximab for ITP is summarized. This case highlights that recognition of more subtle or rare symptoms of rituximab-induced serum sickness is important to facilitate rapid intervention.